MtNF-YC6 and MtNF-YC11 are involved in regulating the transcriptional program of arbuscular mycorrhizal symbiosis - Deng, Chen; Li, Chun-Jui; Hsieh, Chen-Yun; Liu, Li-Yu Daisy; Chen, Yi-An; Lin, Wei-Yi (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi are obligate symbionts that transfer mineral nutrients to host plants through arbuscules, a fungal structure specialized for exchange for photosynthetic products. MtNF-YC6 and MtNF-YC11, which encode the C subunits of nuclear factor Y (NF-Y) family in Medicago truncatula are induced specifically by arbuscular mycorrhizal symbiosis (AMS). A previous study showed that MtNF-YC6 and MtNF-YC11 are activated in cortical cells of mycorrhizal roots, but the gene functions were unknown. Herein, we identified both MtNF-YB17 and MtNF-YB12 as the interacting partners of MtNF-YC6 and MtNF-YC11 in yeast and plants. MtNF-YB17 was highly induced by AMS and activated in cortical cells only in mycorrhizal roots but MtNF-YB12 was not affected. The formation of B/C heterodimers led the protein complexes to transfer from the cytoplasm to the nucleus. Silencing MtNF-YC6 and C11 by RNA interference (RNAi) resulted in decreased colonization efficiency and arbuscule richness. Coincidently, genes associated with arbuscule development and degeneration in RNAi roots were also downregulated. In silico analysis showed CCAAT-binding motifs in the promoter regions of downregulated genes, further supporting the involvement of NF-Y complexes in transcriptional regulation of symbiosis. Taken together, this study identifies MtNF-YC6- or MtNF-YC11-containing protein complexes as novel transcriptional regulators of symbiotic program and provides a list of potential downstream target genes. These data will help to further dissect the AMS regulatory network.